THE IMPROVEMENT OF CREATIVE INDUSTRIES-CULINARY SMES IN THE TOURIST DESTINATIONS OF THE GREATER BANDUNG REGION - Munadjat Wardoyo; Aqilah Nurul Khaerani Latif (ASEAN Journal on Hospitality and Tourism, 2018)
Abstract. This research aims as consideration in formulating policies, regulations, strategies, and culinary tourism feasibility studies to be sustainable. The development of culinary products as a model for culinary tourism development in Indonesia. It aims to improve the welfare of small and medium creative industries in the food and beverage sector in the Greater Bandung area. Data collection techniques with direct interviews and questionnaires. The data analysis method used is the SWOT analysis. The results of this study indicate that culinary business opportunities in the Greater Bandung Region are considered high, but the lack of capital, knowledge, and regulations that are still lacking makes culinary SMEs in Bandung less developed. Some things that must be considered by SMEs to support business, namely knowledge, and experience, product uniqueness, product innovation, capital, courage to do business.